2010
DOI: 10.1021/nn100279j
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature, Highly Efficient Growth of Carbon Nanotubes on Functional Materials by an Oxidative Dehydrogenation Reaction

Abstract: In many applications like photovoltaics, fuel cells, batteries, or interconnects in integrated circuits carbon nanotubes (CNTs) have the role of charge transport electrodes. The building of such devices requires an in situ growth of CNTs at temperatures where the structure or chemical composition of the functional materials is unaltered. We report that in a chemical vapor deposition process involving an oxidative dehydrogenation reaction of C2H2 with CO2 growth temperatures below 400 degrees C are achieved. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 31 publications
(51 reference statements)
2
69
0
Order By: Relevance
“…[50,62,85] Recently, Magrez et al demonstrated that it is possible to grow high-quality MWCNTs by CCVD at 400 8C when adding CO 2 to C 2 H 2 in stoichiometric amounts. [102] The formation of solid carbon occurs by oxidative dehydrogenation of acetylene instead of its dehydrogenation or pyrolysis. The addition of CO 2 favors the reaction thermodynamically (Figure 3 b).…”
Section: Possible Reactions and Corresponding Thermodynamicsmentioning
confidence: 99%
“…[50,62,85] Recently, Magrez et al demonstrated that it is possible to grow high-quality MWCNTs by CCVD at 400 8C when adding CO 2 to C 2 H 2 in stoichiometric amounts. [102] The formation of solid carbon occurs by oxidative dehydrogenation of acetylene instead of its dehydrogenation or pyrolysis. The addition of CO 2 favors the reaction thermodynamically (Figure 3 b).…”
Section: Possible Reactions and Corresponding Thermodynamicsmentioning
confidence: 99%
“…The surface properties of the catalyst were consequently tailored such that the CVD process is more selective for the deposition of highly graphitic nanotubes. 30,31 …”
Section: Introductionmentioning
confidence: 99%
“…For example, when normalised to unit dimension, they exhibit about 10 3 times better current carrying capacity than copper, twice the thermal conductivity of diamond, 30 times lower fi eld-emission threshold voltage than molybdenum tips, and only half the material density of aluminium, but more than 20 times the tensile strength of steel alloys. [1][2][3] Nanotubes are also not compromised by native surface oxide insulating layers, and can be chemically functionalized, even in the plasma phase, in order to optimise their chemical compatibility with a range of organic materials. In particular, the electrical characteristics of MWNCTs make them ideal for enhancing the electrical properties of organic semiconductors using simple mixing techniques.…”
Section: Introductionmentioning
confidence: 99%